Inovasi Manajemen Pendidikan Islam dalam Meningkatkan Mutu Pendidikan dan Karakter Santri di Pondok Pesantren Al-Mustofa Jember - Widodo, Wahyudi (YASIN, 2025)
In facing global challenges, pesantren must continue to innovate through the management of their Islamic education without having to abandon the culture of students. So that with that achievement will be more directed related to the quality of education and the character of students. This study uses a qualitative type of descriptive with the location of PP Al-Mustofa. The sources used are interviews, and observations. The results obtained are: 1) Innovation in Islamic education management at PP Al-Mustofa Jember for the strengthening of students there are four important things which include planning that must be known by all residents of the pesantren including students and guardians, organization that must involve all including the community and guardians and have complete infrastructure. The implementation of pesantren activities is carried out every day from Monday to Sunday. Where in the implementation there is also mandatory daily habituation, special activities in addition to core activities related to book learning. In addition, it is necessary to have an evaluation of the pesantren carried out every two months and a major evaluation every year that invites all the pesantren administrators involved. 2) The forms of Islamic education management innovations of PP Al-Mustofa Jember in improving the quality of teaching and education of students in general are four things, namely: the integration of technology in learning and pesantren so that teachers are required to always use technology as an enhancer to explain the material so that it can make it easier for students to learn, curriculum changes that adjust to pesantren and national traditions, student-oriented learning approaches and 21st century skill development through trainings such as design, business, making tempeh staples, agriculture, plantations, and the development of the Englsh language.